Analisis Kelayakan Penerapan Inklusivitas Kota Ramah Pejalan Kaki di Surabaya: Studi Komparatif dengan Kota Bandung dalam Teori Kepublikan - Handoko, Adistyaisah Maura Filza; Primar, Septha Novita Candrawati; Taurisna, Ismedhika Kartika Candra; Dewi, Salsabila Putriana (Ikatan Da'i Indonesia, 2024)
This research discusses the concept of a pedestrian-friendly city or Walkable City in Surabaya, relating it to Bandung. Based on the Most Liveable City Index (MLCI), Bandung ranks at the Average Tier City level, indicating it has the best city implementation in Indonesia. Similarities in city layout, road conditions, and the economic characteristics of the population suggest that Surabaya and Bandung have similar city identities. This research employs qualitative methods with content analysis techniques to analyze data and interpret the meaning behind data and information from social media users. The findings reveal that Jalan Braga retains a historical impression and features pedestrian-friendly sidewalks, including inclusive public spaces and street designs. However, the lighting on Jalan Braga is dim, causing visitors to feel anxious at night. In Surabaya, especially on Jalan Tunjungan, the walkable city conditions are similar to Jalan Braga. However, the crossing lights are ineffective, and the lack of canopies along the sidewalks discourages walking during the day due to the extreme heat, which is a drawback for implementing a walkable city on Jalan Tunjungan.This research suggests that to improve safety, resilience, and sustainability in inclusive road and urban traffic design comprehensively, the integration framework needs to be expanded beyond conventional views—limited to technology or products, business or economics, and infrastructure or platforms—to encompass space, speed, and priority. Each of these factors directly influences accessibility, security, and social usability and has a reciprocal and interdependent relationship with the others.